(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
As in life, so in history, women get relatively lesser place in our male-dominated society. In the 1920s, the struggle for our freedom became a mass movement. Almost every class, community and group was attracted towards it and their representatives joined it in pretty large numbers. How could the Indian women lag behind in such a situation? In other words, the main effort here is to see how the Punjabi women reacted to the Gandhian struggle for swaraj during this period, the last fight for swaraj. The social base of women’s struggle for it increases manifold in this period. This phenomenon and several other issues such as Muslim Women’s effort in working for the division of the country etc. are explained at length here.